Cardio-toxicity in childhood cancer survivors “Cure is not enough” - Neudorf, Ulrich; Schönecker, Anne; Reinhardt, Dirk (Journal of Thoracic Disease, 2018)
The number of pediatric cancer survivors is growing, and they are getting older. Therapy-induced cardiotoxicity therefore is debated as an ongoing problem. Recognition of the side effects in the use of anthracyclines and radiation as well as the patients’ clinical condition and comorbidities leads back as far as the beginning of systematic cancer treatment in children in the 1980s. Since, numerous case reports, meta-analyses and retrospective surveys were published worldwide. However, randomized clinical trials with standardized protocols yet fail to be designed. This article gives an overview of the recent reports and emphasizes on the heterogeneity of the different approaches. A standardized work-up which may identify the patient at risk—including the patient’s history and condition, individual genetic dispositions, dosage and method of drug application, consideration of co-medication, radiation therapy and dose, standardized imaging methods—is the main proposition of our report. The fusion of already established sources, e.g., data of different registries or study centers, might help to create preventive strategies for and a better understanding of patients with therapy induced cardiomyopathy.